PENERAPAN SISTEM MANAJEMEN MUTU BERDASARKAN STANDAR ISO 9001 : 2005 - Shakina Nur Fitriyna; Lenggogeni Lenggogeni; R. Eka Murtinugraha (Teknik Sipil, Fakultas Teknik Universitas Negeri Jakarta, 2018)
This study aims to find out how the implementation of quality management system based on clause in ISO 9001: 2015 on podomoro golf project development project cimanggis with PT. Wijaya Karya Building Building as a contractor. This study is descriptive using clauses in ISO 9001: 2015 as a way of knowing the implementation of quality management system from owner, construction management consultant, and contractor, with questionnaire form about application of field. Questions are made in clauses 4 to clause 10 in ISO 9001: 2015.The results in this study indicate that the implementation of quality management system based on clause in ISO 9001: 2015 from the owner is